Cardiovascular and nephrological risk in patients with chronic kidney disease in ambulatory care. - O. Kuryata; V. Semenov (Medičnì Perspektivi)
Patients with chronic kidney disease (CKD) have higher than in general population all-cause and cardiovascular mortality. Arterial hypertension (HTN) is a powerful potentially modifiable risk factor that affects the majority of patients with chronic kidney disease and one of the main causes of end stage renal disease worldwide. Existing tools for assessment of risk of CKD progression do not take into account arterial hypertension. The aim – to investigate the association between cardiovascular and nephrological risk factors in patients with CKD in ambulatory practice. The study was carried out in the Center of Nephrology Care in Mechnikov Dnipropetrovsk Regional Hospital, Dnipro, Ukraine. 278 patients (114 males and 164 women, aged 41 [31;61] years) with CKD (stages 1-3) who were followed-up in ambulatory care, but required diagnosis or treatment revision were enrolled to the study. All patients were examined and followed-up according to local and European standards. Females slightly prevailed in our study, gender distribution varied insufficiently in groups by CKD progression risk. Elevation of risk of CKD progression was accompanied by rise of prevalence of diabetes mellitus, left ventricle hypertrophy, proteinuria and HTN.  Risk of CKD progression correlated with age, systolic and diastolic blood pressure, erythrocyte sedimentation rate, total cholesterol, glomerular filtration rate, albumin excretion rate, duration of HTN and body mass index. Rise of cardiovascular risk was accompanied by rise of proportion of patients with high risk of CKD progression. Increase in risk of CKD progression is associated with rise of burden of cardiovascular risk factors. HTN and blood pressure values should be accounted for assessment of risk of CKD progression.